IMPLEMENTASI PERATURAN WALIKOTA NOMOR 39 TAHUN 2014 TENTANG PELAKSANAAN PENATAAN TOKO SWALAYAN DI KOTA SEMARANG (STUDI KASUS PENATAAN MINIMARKET KECAMATAN TEMBALANG) - Rd M Ferrizqi Adzanny; Aufarul Marom (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2019)
The existence of a modern store if it continues to be allowed, is the micro business actor who will feel the most tangible impact. This also affects the position of traditional markets which are oppressed by unbalanced business competition. As an effort to organize self-service shops in the Semarang City Regulation No. 39 of 2014 the regulation stipulates that the distance between minimarkets and traditional markets is at least 500 meters, the distance between minimarkets and traditional cities is at least 95 meters, while the distance between minimarket is at least 50 meters The research design used is qualitative by using a type of analytical descriptive research. The concept of policy implementation in the arrangement of supermarkets can be viewed from the contents of the regulations are location, distance, and access. Factors that encourage and inhibit the implementation of Semarang Mayor Regulation Number 39 of 2014 concerning Implementation of Supermarket Stores in Tembalang District in terms of Grindlee and Edward III theories include communication, resources, disposition, and policy content. The results of the study show the implementation of the Mayor of Semarang Regulation Number 39 of 2014 concerning the Implementation of Supermarket Stores in Tembalang District from the location and access not in accordance with Perwal and not yet going well enough. The Semarang Office of Trade and DPMPTSP has not been able to carry out the implementation of the Perwal policy properly because of the limited human resources and facilities and infrastructure available. In addition, the lack of direct communication intensity is intertwined between implementers. Semarang City Trade Service Office lacks staff especially in the market supervision section.